2010
DOI: 10.1097/hcr.0b013e3181be7e47
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Value of NYHA Functional Class and Quality-of-Life Questionnaire Scores in Assessing Heart Failure

Abstract: Cardiopulmonary exercise variables and plasma NT-proBNP are associated more with NYHA functional class and SAQ score than with MLHF score. When combined, SAQ score, NT-proBNP, and etiology of heart failure can satisfactorily predict peak oxygen uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Moreover, overall lifestyle habits were defined using standard procedures. Body-surface area was calculated [BSA = (height) 0.725 * (weight) 0.425 * 0.007184] and the New York Heart Association (NYHA) functional classification system was used to categorize all CHF patients [19]. In all statistical analysis, continuous measurements were used for blood pressure and biochemical parameters.…”
Section: Measurementsmentioning
confidence: 99%
“…Moreover, overall lifestyle habits were defined using standard procedures. Body-surface area was calculated [BSA = (height) 0.725 * (weight) 0.425 * 0.007184] and the New York Heart Association (NYHA) functional classification system was used to categorize all CHF patients [19]. In all statistical analysis, continuous measurements were used for blood pressure and biochemical parameters.…”
Section: Measurementsmentioning
confidence: 99%
“…Recent studies have assessed whether peak VO 2 can be predicted, [5][6][7][8][9] but to our knowledge, none has assessed whether AT or VE/VCO 2 slope can be predicted. It would be important to be able to predict these measures because Gitt et al 10 have shown that an AT lower than 11 mL·kg -1 ·min -1 and a VE/VCO 2 slope greater than 34 are better predictors than peak VO 2 for risk of early death.…”
Section: Discussionmentioning
confidence: 94%
“…Athanasopoulos et al 5 previously showed that the relation of MLHF score (r s ϭ -0.312, P Ͻ .05) with peak VO 2 was less strong than with SAQ score (r s ϭ 0.647, P Ͻ .001). 5 This may explain why only SAQ score could enter the multivariable model. Plasma NT-proBNP levels and etiology of HF (ischemic/dilated cardiomyopathy) were also individually related to AT with the former having an independent association.…”
Section: Roc Analysismentioning
confidence: 99%
See 2 more Smart Citations